Syria as an arena of strategic competition - Martini, Jeffrey (Rand Corporation, 2013)
"With the regional balance of power hinging on the outcome of the Syrian uprising, RAND conducted an analytic exercise to generate a greater understanding of how external actors are shaping the conflict."--Rand Corporation web site